2020
DOI: 10.21203/rs.3.rs-95087/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overview of Statistical and Machine Learning Techniques for Determining Causes of Death from Verbal Autopsies: A Systematic Literature Review

Abstract: Background: The process of determining causes of death in areas where there is limited clinical services using verbal autopsies has become a key issue in terms of accuracy on cause of death (prone to errors and subjective), quality of data among many drawbacks. This is mainly because there is no proper standard available in performing verbal autopsy, even though it is important for civil registration systems and strengthening of health priorities. Physician diagnosis is the only gold standard in reviewing verb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…After completion of the VA interview, data from the VA questionnaire is then interpreted to assign the cause of death. Methods for assigning the cause of death from the VA interview data vary and include the use of either physician certified verbal autopsies(PCVA) or computer coded verbal autopsy (CCVA) systems that utilise algorithms, statistical techniques, machine learning and deep learning approaches 9 , 10 . A systematic review comparing PCVAs with various CCVA systems found that although the methods differed in the cause of death output, none of the VA interpretation methods reviewed was superior to the others 9 .…”
Section: Introductionmentioning
confidence: 99%
“…After completion of the VA interview, data from the VA questionnaire is then interpreted to assign the cause of death. Methods for assigning the cause of death from the VA interview data vary and include the use of either physician certified verbal autopsies(PCVA) or computer coded verbal autopsy (CCVA) systems that utilise algorithms, statistical techniques, machine learning and deep learning approaches 9 , 10 . A systematic review comparing PCVAs with various CCVA systems found that although the methods differed in the cause of death output, none of the VA interpretation methods reviewed was superior to the others 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study we present a robust machine learning framework for determining causes of death only from VA narratives. We apply effective data cleaning strategies, data balancing to achieve optimum transparency and accuracy through addressing most model limitations and applying recommendations that are reported in [6,7,8]. We assess the robustness of several classifiers including; random forest (RF), k-nearest neighbour (KNN), decision tree (DT), support vector machine (SVM), logistic regression (LR), artificial neural network (ANN), Naive Bayes (NB) and bagging as an ensemble classifier.…”
Section: Introductionmentioning
confidence: 99%